Sedation and Anesthesia Mediated by Distinct GABA(A) Receptor Isoforms - Reynolds, David S. (J Neurosci, 2003)
The specific mechanisms underlying general anesthesia are primarily unknown. The intravenous general anesthetic etomidate acts by potentiating GABA(A) receptors, with selectivity for β2 and β3 subunit-containing receptors determined by a single asparagine residue. We generated a genetically modified mouse containing an etomidate-insensitive β2 subunit (β2 N265S) to determine the role of β2 and β3 subunits in etomidate-induced anesthesia. Loss of pedal withdrawal reflex and burst suppression in the electroencephalogram were still observed in the mutant mouse, indicating that loss of consciousness can be mediated purely through β3-containing receptors. The sedation produced by subanesthetic doses of etomidate and during recovery from anesthesia was present only in wild-type mice, indicating that the β2 subunit mediates the sedative properties of anesthetics. These findings show that anesthesia and sedation are mediated by distinct GABA(A) receptor subtypes.